Energy Transformation in the Dairy Industry Towards Process Efficiency and Environmental Impact Reduction - Raisha, Rajwa Ruhing; Rafi Umara, Dimas; Nurhayati, Indah; Inayatus Sa‘idah, Archil (Universitas Negeri Semarang, 2025)
The dairy industry is among the most energy-intensive sectors within the food processing chain, relying heavily on fossil fuels for heating, cooling, and packaging operations. In response to global sustainability challenges and climate targets, this review explores integrated strategies for energy transformation in the dairy sector, focusing on renewable energy adoption, waste valorization, and digital technologies. Emphasis is placed on the use of soybean hulls—a rich source of lignocellulosic biomass—as feedstock for bioethanol production through a sequence of pretreatment, hydrolysis, fermentation, and distillation processes. Additionally, the role of biogas and solar energy integration, along with energy recovery systems and IoT-based monitoring, is analyzed for improving operational efficiency. The findings reveal that such transformations can reduce greenhouse gas emissions, lower operational costs, and increase energy self-sufficiency, especially when supported by circular economy principles. This review highlights the potential for scaling these solutions in both industrial and small-scale dairy production, offering practical insights into how renewable energy and digital innovation can drive a more competitive, sustainable, and decarbonized dairy industry.